Annual Plan 1996-97 Government of Bihar - Planning Commission (Planning Commission, 1996)
Bihar is the second most populous State of India. According to the Census of 1991, its population is 86. 37 millions which is about 10.2 per cent of the total population of the country. the State covers an area of 1.74 lakh sq.kms which constitutes 5.3 per cent of the total area of the country, There is thus, an imbalance in the land-man ratio which is reflected in the high density of population of the State. The density of population in Bihar was 497 per sq. km. as against 267 for the country. the corresponding figures for 1981 were 402 and 208 respectively. 1.2. Almost half of the total area of the State consists of hills and plateau, while the remaining half is an alluvial plain, divided into two unequal parts, North and South, by the river Ganga.
Planning and Development Department